Targeting Sensory and Motor Integration for Recovery of Movement After CNS Injury - Asan, Ahmet S.; McIntosh, James R.; Carmel, Jason B. (Frontiers in Neuroscience, 2022)
The tight interaction of the sensory and motor systems, known as sensory-motor integration (SMI) is a prerequisite for learning and performing movement. Coordinated activation of sensory and motor systems modifies the neural networks in the CNS and enables the acquisition of skilled movements. Injury to various nodes of the sensorimotor network causes impairment in movement execution and learning. Stimulation methods have been developed to recruit the sensorimotor system and restore movement after CNS injury. This paper will review the main processes and anatomical interactions responsible for SMI in health. We then discuss the effects of injury on sites critical for SMI, including the spinal cord, cerebellum, and cerebral cortex. Finally, we will review the application of activity-dependent plasticity in ways that specifically target integration of sensory and motor systems. Employing treatments based on the mechanisms of SMI and learning could advance strategies to improve rehabilitation after injury.